A comparative analysis in monitoring 24-hour urinary copper in Wilson disease: sampling on or off treatment? - Mohr, Isabelle; Lamadé, Patrick; Weber, Christophe; Leidner, Viola; Köhrer, Sebastian; Olkus, Alexander; Lang, Matthias; Langel, Andrea; Dankert, Patrischia; Greibich, Melanie; Wolf, Silke; Zimmer, Holger; et al. (Orphanet journal of rare diseases, 2025)
Twenty-four-hour urinary copper excretion (24 h-UCE) is the standard diagnostic tool for dose adjustments in maintenance therapy in Wilson disease (WD) patients. Guidelines lack data if both variants of 24 h-UCE measurement (with or without 48 h of treatment interruption) are equally interpretable.
Veröffentlicht: 21. Januar 2025
Gesehen am 15.04.2025